EEG alpha measures predict therapeutic response to an SSRI antidepressant: Pre and post treatment findings - Bruder, Gerard E. (2007)
BACKGROUND: There is growing evidence that individual differences among depressed patients on electrophysiologic (EEG), neuroimaging, and neurocognitive measures are predictive of therapeutic response to antidepressants. This study replicates prior findings of pretreatment differences between SSRI responders and nonresponders in EEG alpha power or asymmetry, and examines whether these differences normalize or are stable following treatment. METHODS: Resting EEG (eyes open and closed) was recorded from 28 electrodes (nose reference) in 18 depressed patients when off medication and at the end of 12 weeks of fluoxetine treatment. Clinical response was assessed by an independent rater using the Clinical Global Improvement scale. EEG data were also obtained for 18 healthy adults matched to patients in gender and age. RESULTS: Treatment responders had greater alpha power compared to nonresponders and healthy controls, with largest differences at occipital sites where alpha was largest. There were also differences in alpha asymmetry between responders and nonresponders at occipital sites. Responders showed greater alpha (less activity) over right than left hemisphere, whereas nonresponders tended to show the opposite asymmetry. Neither alpha power nor asymmetry changed following treatment and test-retest correlations were high, particularly for alpha power. Alpha power and asymmetry showed reasonable positive predictive value but less negative predictive value. DISCUSSION: The findings confirm reports of alpha differences between antidepressant responders and nonresponders, and raise hopes for developing EEG tests for selecting effective treatments for patients. The stability of alpha power and asymmetry differences between SSRI responders and nonresponders following treatment suggests that they represent state-independent characteristics. CLINICAL TRIALS: Prozac treatment of major depression: discontinuation study; registration #NCT00447128; and Dichotic listening as a predictor of placebo and medication response in depression; registration #NCT00296725; http://www.clinicaltrials.gov/.